Pelatihan Mengenal Warna Melalui Rainbow Walking Water Di KB IZZATI BEKASI - Khofifah, Nisa (Jurnal Pengabdian Masyarakat PGSD, 2023)
Aspects of cognitive development is one aspect that is very important for children, one of which is in recognizing colors. the background of this training is the lack of understanding of children in the IZZATI KB in recognizing colors. The method used in the Rainbow walking water training is direct demonstration and practice. This training aims to help children develop cognitive aspects of children, namely color recognition. This training was held at KB IZZATI Kampung Beting, Pantai Bahagia Village, Muara Gembong District, Bekasi Regency, with the target of training 2 teachers and 18 children aged 5-6 years. The stages in this training are divided into three stages, namely (1) preparation, (2) implementation stage, (3) evaluation and reporting stage. From the results of this training it can be concluded that cognitive development in the IZZATI KB is well developed, there is influence from the Rainbow walking water training method.